2011
DOI: 10.1534/genetics.110.124073
|View full text |Cite
|
Sign up to set email alerts
|

Inference of Mutation Parameters and Selective Constraint in Mammalian Coding Sequences by Approximate Bayesian Computation

Abstract: We develop an inference method that uses approximate Bayesian computation (ABC) to simultaneously estimate mutational parameters and selective constraint on the basis of nucleotide divergence for proteincoding genes between pairs of species. Our simulations explicitly model CpG hypermutability and transition vs. transversion mutational biases along with negative and positive selection operating on synonymous and nonsynonymous sites. We evaluate the method by simulations in which true mean parameter values are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Certain authors have compared substitution rates at synonymous sites to substitution rates at a presumed neutral control, such as ancestral repeats. They have concluded that 20–25% of synonymous sites are under purifying selection (Eory et al 2010 ; Keightley et al 2011 ) [though see also Price and Graur ( 2016 ), who argue that few if any synonymous sites are under selection]. However, these studies assumed that all mutations were either neutral or sufficiently deleterious to preclude substitutions completely.…”
Section: Discussionmentioning
confidence: 99%
“…Certain authors have compared substitution rates at synonymous sites to substitution rates at a presumed neutral control, such as ancestral repeats. They have concluded that 20–25% of synonymous sites are under purifying selection (Eory et al 2010 ; Keightley et al 2011 ) [though see also Price and Graur ( 2016 ), who argue that few if any synonymous sites are under selection]. However, these studies assumed that all mutations were either neutral or sufficiently deleterious to preclude substitutions completely.…”
Section: Discussionmentioning
confidence: 99%
“…We first measured the strength of the selective constraint C = 1 – (π NS /π S ) (Keightley et al ., , also known as evolutionary constraint) from the diversity at non‐synonymous (π NS ) and synonymous sites (π S ), assuming the latter to be neutral.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a shift in fitness model has a minimal effect on the results since fixations are extremely rare (<0.3% of the mutations) during the 400 generations followed here. In addition, this model has recently been shown to be a realistic fit to human mutation load (Keightley et al 2011; Lesecque et al 2012). We refer to derived alleles ( i.e.…”
Section: Methodsmentioning
confidence: 99%